Three new species of Tagalis Stål (Hemiptera: Heteroptera: Reduviidae: Saicinae) from Brazil HÉLCIO R. GIL-SANTANA (Brazil) - Gil-Santana, Hélcio R. (Zootaxa, 2011)
Tagalis baenai sp. nov., T. grossii sp. nov. and T. marquesi sp. nov. from Brazil are described. Morphological variations and male genitalia of Tagalis inornata inornata Stål, 1860, are described. A revised key to the species of Tagalis Stål, 1860, is presented.